2010
DOI: 10.1093/eurpub/ckp231
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to HIV testing in Europe: a systematic review

Abstract: Some barriers to HIV testing and counselling have been illustrated in the literature. Nevertheless, there is lack of structured information on barriers considering (i) legal, administrative and financial factors, (ii) attitudes and practices of health care providers and (iii) perception of patients. Such data is critical to improve effectiveness of HIV testing and counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
234
3
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(276 citation statements)
references
References 38 publications
21
234
3
11
Order By: Relevance
“…Consistent with prior research, factors identified as barriers to HIV testing included misperceptions about HIV, lack of knowledge on the importance of knowing one's HIV status, lack of access to testing, and fears of deportation [24][25][26][27]. These factors have been found in other studies among vulnerable groups as barriers to HIV testing [6,[28][29][30].…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with prior research, factors identified as barriers to HIV testing included misperceptions about HIV, lack of knowledge on the importance of knowing one's HIV status, lack of access to testing, and fears of deportation [24][25][26][27]. These factors have been found in other studies among vulnerable groups as barriers to HIV testing [6,[28][29][30].…”
Section: Discussionsupporting
confidence: 76%
“…Low risk perception is a commonly cited barrier to HIV testing regardless of age, highlighted in a previous review. 29 However, despite disclosing HIV risk behaviours, some patients still perceive themselves to be low risk. 30,12 In the older population, this low perceived risk may be exacerbated by the perception HIV is a young person's disease.…”
Section: Discussionmentioning
confidence: 99%
“…The stigma associated aggravates the negative view that young people have of the disease. This catastrophic social perception 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 has been found to be the main reason for not testing in a recent review in Europe (67).…”
Section: Insert Table IImentioning
confidence: 99%